Food hygiene steps of a new republic (meat inspection methods) - Genc, Savas Volkan; Goltas, Gizem (Progress in Nutrition, 2022)
Study Objectives: In this study, it was aimed to announce a historically important source in meat inspection, which is a very important area of healthy eating, and the positive developments experienced thanks to this source to the scientific world. Methods: In this study, which was designed as document analysis, one of the qualitative research patterns, a historical book on meat inspection was examined. Results: With its establishment, the Republic of Turkey has entered development and enlightenment in all areas. In this period when veterinary services were started to be reconsidered, one of the first studies was about food range. A book called “Meat Inspection Methods and Booklet about the Causes Seizure” was published by Şevki Bey who was a Veterinary School Lecturer of Pathology and Meat Inspection in Istanbul. Consisting of two parts, the booklet includes a wide scope of animals from slaughtered birds, pet rabbits, fishes, and other aquatic products, hunting animals in the country to horse meat which is not consumed by people in that country. The author has mentioned neglecting food hygiene for a long period, and despite the significant knowledge, he has also stressed that there is a lack of legislative regulation. Although the work is short, the enabling legislation has been compared in Switzerland, Belgium, Germany, and France. Conclusion: Şevki made a warning on an area of veterinary medicine for the healthy and rich life of a newly founded nation that suffered under great battles for many years.